Halogen-free flame-retardant resin composition, prepreg containing halogen-free flame-retardant resin composition, metal foil-coated laminated board and printed circuit board
By introducing modified benzooxazine prepolymer and side chain epoxy-modified silicone oil in the halogen-free low-dielectric material, the problems of slow curing reaction and bonded sheet-deficient resin in the existing materials are solved, and higher reactivity and better heat resistance are achieved.
Patent Information
- Application Number
- CN202411974174.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing halogen-free low-dielectric materials have high water absorption and CTE, poor flame retardancy, and the benzoxazine resin curing reaction temperature and slow reaction rate, which can easily lead to insufficient curing of the bonded sheet, resulting in insufficient Tg of the sheet and reduced heat resistance.
Modified benzooxazine prepolymer and side chain epoxy-modified silicone oil, combined with epoxy resin and low dielectric curing agent, form a halogen-free flame retardant resin composition to improve reactivity and avoid the problem of bonded sheet resin deficiency.
The reactivity of the low-polar epoxy resin composition is significantly improved, and the problem of lack of resin on the bonded sheet is avoided. At the same time, the peel strength of the sheet and the heat resistance between layers are maintained, thereby improving the overall performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laminated boards, and relates to a halogen-free flame-retardant resin composition, a prepreg containing the same, a metal foil-clad laminated board and a printed circuit board. Background Art
[0002] The current halogen-free low-dielectric materials are basically based on the technical route of epoxy resin and composite curing agent. In addition to the contribution of epoxy resin itself, low-dielectric curing agent is the most commonly used technical means to reduce the dielectric constant, and acid anhydride compounds are the first choice. However, the water absorption rate and CTE of acid anhydride compounds are relatively high, and the flame retardancy is poor. Therefore, the industry will use benzoxazine resin as a co-curing agent for epoxy resin to improve the performance of the resin composition in terms of water absorption, CTE and flame retardancy. Although benzoxazine has many advantages, it has the following disadvantages: benzoxazine resin has high curing reaction temperature and slow curing reaction rate, which can easily lead to insufficient resin curing of the bonding sheet during the hot pressing process, resulting in insufficient Tg of the board and reduced heat resistance.
[0003] CN116515065A discloses an epoxy resin / prepolymerized benzoxazine copolymer and a preparation method thereof. Although the benzo prepolymer can improve the reactivity of benzoxazine with epoxy resin, it will cause the bonding sheet to lack resin.
[0004] CN116376230A discloses a resin glue, prepreg, metal foil-clad laminate and printed circuit board. Although modified silicone oil can help improve the resin deficiency problem of the adhesive sheet of the low-polarity resin system, it will cause the peel strength and interlayer heat resistance of the board to decrease.
[0005] Therefore, in the art, it is desired to develop a resin composition, a prepreg, and a laminate material that can improve the reactivity of epoxy resin and benzoxazine curing system and improve the appearance of the bonding sheet. Summary of the invention
[0006] In view of the deficiencies of the prior art, the object of the present invention is to provide a halogen-free flame retardant resin composition, a prepreg containing the same, a metal foil-clad laminate and a printed circuit board.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In one aspect, the present invention provides a halogen-free flame retardant resin composition, wherein the halogen-free flame retardant resin composition comprises the following components in parts by weight:
[0009] Epoxy resin A: 100 parts by weight;
[0010] Low dielectric curing agent B: 10-75 parts by weight;
[0011] Benzoxazine prepolymer C: 5-40 parts by weight;
[0012] Side chain epoxy modified silicone oil D: 0.001-5 parts by weight;
[0013] Phosphorus-containing flame retardant E: 20-50 parts by weight.
[0014] In the present invention, by introducing modified benzoxazine prepolymer and silicone oil modified with epoxy groups in the side chain, the reactivity of the low-polarity epoxy resin composition can be greatly improved, and the problem of lack of resin in the bonding sheet can be avoided. In addition, since the modified silicone oil contains epoxy side chains, the compatibility of the silicone oil segment with the matrix epoxy can be improved, thereby not deteriorating the peel strength and interlayer heat resistance of the board.
[0015] Preferably, the epoxy resin is selected from any one of trifunctional epoxy resins or tetrafunctional epoxy resins or a combination of at least two thereof.
[0016] In the present invention, the epoxy resin is selected from any one or a combination of at least two of dicyclopentadiene epoxy resin, dimethylphenol novolac epoxy resin, tetramethyl biphenyl epoxy resin, biphenyl epoxy resin, novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, epoxy resin containing C1-C6 alkyl, MDI modified epoxy resin, epoxy resin containing naphthalene ring or epoxidized polybutadiene.
[0017] In the present invention, relative to 100 parts by weight of epoxy resin A, the content of the low dielectric curing agent B is 10-75 parts by weight, for example, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight or 75 parts by weight.
[0018] In the present invention, the low dielectric curing agent includes anhydride curing agent and / or active ester curing agent.
[0019] Preferably, the anhydride curing agent is selected from any one of the following B11 or B12 or a combination of at least two:
[0020]
[0021] Among them, n:x=1:1~8:1 (for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1).
[0022] B12 is a copolymer resin having a structural unit derived from an aromatic vinyl compound and a structural unit derived from maleic anhydride.
[0023] Preferably, the content of anhydride curing agent in the low dielectric curing agent is 1-50 parts by weight, for example, it can be 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight or 50 parts by weight.
[0024] Preferably, the active ester curing agent is selected from any one or a combination of at least two of the active esters having the following B21 or B22 structures:
[0025]
[0026] In B21, X is phenyl or naphthyl, j is 0 or 1, k is 0 or 1, and n represents a repeating unit of 0.25 to 1.25 (e.g., 0.25, 0.50, 0.80, 1.0, 1.1, 1.2 or 1.25);
[0027]
[0028] In B21, m, n, and q are independently integers of 1 to 6 (e.g., 1, 2, 3, 4, 5, or 6), X is phenyl or naphthyl, and Y is the following group:
[0029] Where K is 0 or 1.
[0030] In the present invention, the benzoxazine prepolymer C may be a benzoxazine oligomer containing phenolic hydroxyl groups generated by self-polymerization of benzoxazine monomers, or a prepolymer formed by further copolymerization of benzoxazine oligomers with epoxy resins.
[0031] Preferably, the number average molecular weight Mn of the benzoxazine prepolymer is 500-1000, for example: 500, 520, 540, 560, 580, 600, 620, 640, 680, 700, 720, 740, 780, 800, 820, 840, 860, 880, 900, 920, 940, 960, 980, 1000, etc., and too low number average molecular weight Mn of the benzoxazine prepolymer will lead to poor reactivity and too long GT, which is not conducive to the control of glue GT; too high number average molecular weight will lead to too high reactivity and too short GT, which is not conducive to the control of glue GT.
[0032] GT (gel time) is 50-300s, for example: 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300s, etc. (Test conditions: 0.6±0.1g, 210±1℃, refer to IPC-TM-6502.3.18 standard method). If the gel time GT of benzoxazine prepolymer is too low, the GT of the glue will be too short and the reaction activity will be too high, which cannot meet the normal GT control range requirements; if the gel time GT of benzoxazine is too long, the GT of the glue will be too long, which also cannot meet the normal GT control range requirements.
[0033] In the present invention, relative to 100 parts by weight of epoxy resin A, the content of the benzoxazine prepolymer C is 5-40 parts by weight, for example, 5 parts by weight, 8 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight or 40 parts by weight.
[0034] Preferably, the side chain epoxy-modified silicone oil D has the following structure:
[0035]
[0036] wherein m and n are each an integer greater than 1, such as 1, 2, 3, 4, 5, 6, 8, 10, 11, 16, 19, 20, 30, 50, etc., preferably an integer between 8 and 18;
[0037] R1 is independently selected from the functional groups of the following structures:
[0038]
[0039] R2 is a C1-C5 alkyl group, or a C1-C5 alkyl structure containing an ether bond, or a C1-C5 arylalkyl structure containing a phenyl group, for example: -CH2-, -CH2-CH2-, -CH2-CH2-CH2-, -CH2-CH2-CH2-CH2-, -CH2-CH2-CH2-CH2-CH2-, -CH2-O-, -CH2-CH2-O-, -CH2-CH2-CH2-O-, -CH2-CH2-CH2-CH2-O-, -CH2-CH2-CH2-CH2-O-, -CH2-CH2-CH2-CH2-O-, -CH2-Ph-, -CH2-CH2-Ph-, -CH2-CH2-CH2-Ph-, -CH2-CH2-CH2-Ph-, -CH2-CH2-CH2-Ph-, -CH2-CH2-CH2-CH2-Ph-, -CH2-CH2-CH2-CH2-Ph-, -CH2-CH2-CH2-CH2-Ph-, etc., where -Ph- represents phenyl.
[0040] Preferably, the side chain epoxy-modified silicone oil D can be selected from the organic modified silicone oils produced by Shin-Etsu Chemical Co., Ltd. of Japan: X-22-343, KF-101, KF-1001, X-22-2000, X-22-2046, KF-102, X-22-4741, KF-1002, KF-1005, etc.
[0041] Preferably, the epoxy equivalent of the side chain epoxy modified silicone oil D is ≤4000 g / mol, for example: 4000, 3800, 3600, 3500, 3400, 3300, 3200, 3100, 3000, 2900, 2800, 2700, 2500, 2000, 1500, 1000, 800, 600, 400, 300, 200, etc. Too large an epoxy equivalent will lead to poor compatibility between silicone oil and epoxy resin cured product, cracking of interlayer bonding of the board, and decreased heat resistance.
[0042] In the present invention, relative to 100 parts by weight of epoxy resin A, the content of the side chain epoxy modified silicone oil D is 0.001 parts by weight, 0.005 parts by weight, 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.5 parts by weight, 1 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight. If the amount of the side chain epoxy modified silicone oil is too small, the bonding sheet will lack resin, which is not conducive to the requirements of HDI fine circuits for the apparent quality of the bonding sheet; if the amount is too large, the Tg of the board will decrease, the interlayer adhesion will crack, and the T288 heat resistance will be insufficient.
[0043] Preferably, the phosphorus-containing flame retardant is selected from inorganic phosphorus-containing flame retardants and / or organic phosphorus-containing flame retardants.
[0044] Preferably, the inorganic phosphorus-based flame retardant is selected from any one of red phosphorus, ammonium phosphate, phosphoric acid amide, phosphoric acid or phosphine oxide, or a combination of at least two thereof.
[0045] Preferably, the ammonium phosphate includes any one of monoammonium phosphate, diammonium phosphate or triammonium phosphate, or a combination of at least two of them.
[0046] Preferably, the organic phosphorus flame retardant is selected from any one or a combination of at least two of aromatic phosphates, monosubstituted phosphonic acid diesters, disubstituted phosphinates, metal salts of disubstituted phosphinic acids, cyclic organic phosphorus compounds, or phosphorus-containing phenolic resins. Preferably, any one or a combination of at least two of aromatic phosphates, metal salts of disubstituted phosphinic acids, or phosphorus-containing phenolic resins is selected, and phosphorus-containing phenolic resins are further preferred.
[0047] In the halogen-free flame retardant resin composition of the present invention, relative to 100 parts by weight of epoxy resin A, the amount of the phosphorus-containing flame retardant can be 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight or 50 parts by weight.
[0048] Preferably, the halogen-free flame retardant resin composition further comprises filler F.
[0049] Preferably, the filler is selected from any one or a combination of at least two of aluminum hydroxide, silicon dioxide, talc, boehmite, zeolite, wollastonite, magnesium oxide, calcium silicate, calcium carbonate, clay or mica.
[0050] Preferably, the median particle size of the filler is D50 = 1.8-3.2 μm (e.g., 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3.0 μm or 3.2 μm), and the maximum particle size is D100 = 5.0-15.0 μm (e.g., 5.0 μm, 7.0 μm, 10.0 μm, 12.0 μm, 14.0 μm or 15.0 μm).
[0051] Preferably, the physical form of the filler can be flake, rod, sphere, hollow sphere, granule, fiber or plate.
[0052] In the present invention, the filler may be selectively treated with a silane coupling agent.
[0053] Preferably, in the halogen-free flame retardant resin composition, the content of the filler is 40-400 parts by weight relative to 100 parts by weight of epoxy resin A, for example, it can be 40 parts by weight, 50 parts by weight, 80 parts by weight, 100 parts by weight, 130 parts by weight, 150 parts by weight, 180 parts by weight, 200 parts by weight, 250 parts by weight, 300 parts by weight, 350 parts by weight or 400 parts by weight.
[0054] Preferably, the halogen-free flame retardant resin composition further comprises a curing accelerator G.
[0055] Preferably, the curing accelerator is selected from any one of imidazole accelerators, pyridine curing agents, Lewis acid curing agents, amine curing agents, phenolic curing agents, cyanate compounds or active ester compounds, or a combination of at least two thereof.
[0056] In another aspect, the present invention provides a prepreg, wherein the prepreg comprises the halogen-free flame retardant resin composition as described above.
[0057] Preferably, the prepreg comprises a base material and the halogen-free flame retardant resin composition as described above attached to the base material;
[0058] Preferably, the prepreg comprises a base material and the halogen-free flame retardant resin composition as described above attached to the base material after impregnation and drying.
[0059] In another aspect, the present invention provides a metal foil-clad laminate, comprising at least one prepreg as described above and a metal foil coated on one side or both sides of the laminated prepreg.
[0060] In another aspect, the present invention provides a printed circuit board, comprising at least one of the prepreg as described above or the metal foil clad laminate as described above.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] The halogen-free flame retardant resin composition of the present invention can greatly improve the reactivity of the low-polarity epoxy resin composition and avoid the problem of lack of resin in the bonding sheet by introducing a modified benzoxazine prepolymer and an organic silicone oil modified with an epoxy group in the side chain. In addition, since the modified silicone oil contains an epoxy side chain, the compatibility of the silicone oil segment with the matrix epoxy can be improved, thereby not deteriorating the peel strength and interlayer heat resistance of the board. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0064] The materials and grades involved in the following examples and comparative examples are as follows:
[0065] A1: CNE type epoxy resin (o-cresol epoxy resin): NPCN-704, epoxy equivalent: 200-220g / eq, Nan Ya resin;
[0066] A2: HP-7200HHH, DCPD type epoxy resin, epoxy equivalent: 280-290g / eq, Japan DIC;
[0067] A3: phenol novolac epoxy resin, BNE-200, equivalent weight: 200g / eq, Changchun Resin, Taiwan, China;
[0068] B1: styrene maleic anhydride copolymer: SMA-EF40, Cray Valley, USA;
[0069] B2: Active ester curing agent: DFE-617L, Sichuan Dongcai;
[0070] C1: benzoxazine prepolymer (homemade), Mn: 500, GT: 300s;
[0071] C2: benzoxazine prepolymer (homemade), Mn: 700, GT: 200s;
[0072] C3: benzoxazine prepolymer (homemade), Mn: 900, GT: 100s;
[0073] C4: benzoxazine prepolymer (homemade), Mn: 1000, GT: 50s;
[0074] C5: epoxybenzoxazine prepolymer (homemade), Mn: 1000, GT: 150s;
[0075] C6: benzoxazine prepolymer (homemade), Mn: 1200, GT: 30s;
[0076] C7: benzoxazine resin monomer, (PF3500, Changchun, Taiwan, China), Mn: 450, GT: 400s;
[0077] D1: Epoxy-modified silicone oil: Brand KF-101, Shin-Etsu Chemical, Japan, side chain epoxy structure, epoxy equivalent weight is 350g / mol.
[0078] D2: Epoxy-modified silicone oil: Brand X-22-4741, Shin-Etsu Chemical, Japan, side chain epoxy polyether type, epoxy equivalent weight 2500 g / mol;
[0079] D3: Epoxy-modified silicone oil: Brand KF-102, Shin-Etsu Chemical, Japan, side chain alicyclic epoxy, epoxy equivalent weight is 3600 g / mol.
[0080] D4: Epoxy modified silicone oil: Brand KF-1002, Shin-Etsu Chemical, Japan, side chain epoxy polyether type, epoxy equivalent is 4300g / mol.
[0081] D5: Epoxy-modified silicone oil: Brand KF-22-163, Shin-Etsu Chemical, Japan, terminal epoxy type, epoxy equivalent weight is 200 g / mol.
[0082] D6: Epoxy-modified silicone oil: Brand KF-864, Shin-Etsu Chemical, Japan, side chain amino type, amine equivalent weight is 3800 g / mol.
[0083] E1: Phosphate flame retardant: brand PX200, Japan Daihachi Chemical.
[0084] E2: Phosphorus-containing phenolic resin: Brand XZ92741, DOW Company, USA.
[0085] F: Spherical silica: Q099, D100 is 5μm, Chongqing Jinyi;
[0086] G: Curing accelerator: 2-ethyl-4-methylimidazole, Shikoku Chemical.
[0087] Preparation Example 1: Synthesis of benzoxazine prepolymer C1
[0088] In a 500mL three-necked flask equipped with a stirrer, a condenser and a thermometer, 40g of benzoxazine resin monomer (PF3500, Changchun, Taiwan, China), 0.1g of accelerator (2E4MZ) and 150g of a mixed solution of butanone and xylene (the volume of butanone and xylene is 1:2) were added, stirred evenly, heated to 130°C and kept under reflux for 2h, and the heating was stopped. The resin layer was taken and the solvent was removed by a rotary evaporator to obtain a yellow-brown viscous benzoxazine prepolymer C1. The average number average molecular weight Mn of the benzoxazine prepolymer C1 is 500, and the GT is 300s.
[0089] Preparation Example 2: Synthesis of benzoxazine prepolymer C2
[0090] In a 500mL three-necked flask equipped with a stirrer, a condenser and a thermometer, 40g of benzoxazine resin monomer (PF3500, Changchun, Taiwan, China), 0.1g of accelerator (2E4MZ) and 150g of a mixed solution of butanone and xylene (the volume of butanone and xylene is 1:2) were added, stirred evenly, heated to 130°C and kept under reflux for 3h, and the heating was stopped. The resin layer was taken and the solvent was removed by a rotary evaporator to obtain a yellow-brown viscous benzoxazine prepolymer C2. The average number average molecular weight Mn of the benzoxazine prepolymer C2 is 700, and the GT is 200s.
[0091] Preparation Example 3: Synthesis of benzoxazine prepolymer C3
[0092] In a 500mL three-necked flask equipped with a stirrer, a condenser and a thermometer, 40g of benzoxazine resin monomer (PF3500, Changchun, Taiwan, China), 0.1g of accelerator (2E4MZ) and 150g of a mixed solution of butanone and xylene (the volume of butanone and xylene is 1:2) were added, stirred evenly, heated to 130°C and kept under reflux for 4h, and the heating was stopped. The resin layer was taken and the solvent was removed by a rotary evaporator to obtain a yellow-brown viscous benzoxazine prepolymer C3. The average number average molecular weight Mn of the benzoxazine prepolymer C3 is 900, and the GT is 100s.
[0093] Preparation Example 4: Synthesis of benzoxazine prepolymer C4
[0094] In a 500mL three-necked flask equipped with a stirrer, a condenser and a thermometer, 40g of benzoxazine resin monomer (PF3500, Changchun, Taiwan, China), 0.1g of accelerator (2E4MZ) and 150g of a mixed solution of butanone and xylene (the volume of butanone and xylene is 1:2) were added, stirred evenly, heated to 130°C and kept under reflux for 5h, and the heating was stopped. The resin layer was taken and the solvent was removed by a rotary evaporator to obtain a yellow-brown viscous benzoxazine prepolymer C4. The average number average molecular weight Mn of the benzoxazine prepolymer C4 is 1000, and the GT is 50s.
[0095] Preparation Example 5: Synthesis of epoxy-modified benzoxazine prepolymer C5
[0096] In a 500mL three-necked flask equipped with a stirrer, a condenser and a thermometer, 50g of benzoxazine prepolymer C1 (the product of Synthesis Example 1), 20g of bisphenol A epoxy resin (GELR-128E, Guangzhou Hongchang Electronics), 0.1g of accelerator (2E4MZ) and 150g of a mixed solution of butanone and xylene (the volume of butanone and xylene is 1:2) were added, stirred evenly, heated to 130°C and kept under reflux for 1h, and the heating was stopped. The resin layer was taken and the solvent was removed by a rotary evaporator to obtain a yellow-brown viscous epoxy-modified benzoxazine prepolymer C5. The average number average molecular weight Mn of the epoxy-modified benzoxazine prepolymer C5 is 1000, and the GT is 150s.
[0097] Preparation Example 6: Synthesis of benzoxazine prepolymer C6
[0098] In a 500mL three-necked flask equipped with a stirrer, a condenser and a thermometer, 40g of benzoxazine resin monomer (PF3500, Changchun, Taiwan, China), 0.1g of accelerator (2E4MZ) and 150g of a mixed solution of butanone and xylene (the volume of butanone and xylene is 1:2) were added, stirred evenly, heated to 130°C and kept under reflux for 6h, and the heating was stopped. The resin layer was taken and the solvent was removed by a rotary evaporator to obtain a yellow-brown viscous benzoxazine prepolymer C6. The average number average molecular weight Mn of the benzoxazine prepolymer C6 is 1200, and the GT is 30s.
[0099] The formulation composition and physical property data of each embodiment are shown in Table 1 and Table 2, and the formulation composition and physical property data of the comparative example are shown in Table 3 and Table 4.
[0100] Table 1
[0101]
[0102]
[0103] Table 2
[0104]
[0105]
[0106] Table 3
[0107]
[0108]
[0109] Table 4
[0110]
[0111] Note: In Tables 1 and 2, "NG" means that the T288 test failed, and "OK" means that the 288 test passed.
[0112] The above performance test method is as follows:
[0113] (1) Glue GT: Determined using the test method of IPC-TM-650 standard, method 2.3.18.
[0114] (2) Glass transition temperature: Differential scanning calorimetry (DSC) is used to measure the glass transition temperature according to the DSC method specified in 2.4.25 of IPC-TM-650.
[0115] (3) Dielectric constant (1 GHz): Measured using the parallel plate capacitance method in accordance with the method specified in 2.5.5.9 of IPC-TM-650.
[0116] (4) T288: Use a thermomechanical analyzer and perform the measurement in accordance with the method specified in IPC-TM-650 2.4.24.1.
[0117] (5) Flammability: measured according to the vertical combustion method of UL-94 standard.
[0118] (6) Interlayer adhesion: in accordance with IPC-TM-650 standard, vertical method.
[0119] From the GT performance of the glue: Compared with Example 1, Comparative Example 1 has a relatively small amount of benzoxazine prepolymer, resulting in a too long GT of the glue, and the reactivity is too slow, which will lead to insufficient curing in the subsequent lamination process. Compared with Example 1, Comparative Example 2 has a relatively large amount of benzoxazine prepolymer, resulting in a too short GT of the glue, which cannot meet the normal GT control range requirements. Compared with Example 1, the molecular weight of the benzoxazine prepolymer used in Comparative Example 3 is too large, and the GT of the glue is too short, which cannot meet the normal GT control range requirements. Compared with Example 1, Comparative Example 4 uses unprepolymerized benzoxazine, and the GT is too long, which cannot meet the normal GT control range requirements.
[0120] From the appearance of the bonding sheet: compared with Example 1, the amount of epoxy-modified silicone oil used in Comparative Example 5 is too small, resulting in a lack of resin in the bonding sheet, which is not conducive to the requirements of HDI fine circuits for the appearance quality of the bonding sheet.
[0121] From the performance of the board: Compared with Example 1, the amount of epoxy-modified silicone oil used in Comparative Example 6 is too much, resulting in a decrease in the Tg of the board, cracking of the interlayer adhesion, and insufficient heat resistance of T288. Compared with Example 1, the epoxy equivalent of the epoxy-modified silicone oil used in Comparative Example 7 is too large, resulting in poor compatibility between the silicone oil and the epoxy resin cured product, cracking of the interlayer bonding force of the board, and decreased heat resistance. Compared with Example 1, Comparative Example 8 uses an end-group epoxy-modified silicone oil, which has insufficient crosslinking points with the epoxy resin system, resulting in cracking of the interlayer bonding force of the board and decreased heat resistance. Compared with Example 1, Comparative Example 9 uses a side-chain amino-modified silicone oil, resulting in a lack of resin in its bonding sheet, which is not conducive to the requirements of HDI fine circuits for the apparent quality of the bonding sheet. Compared with Example 1, the amount of phosphorus-containing flame retardant used in Comparative Example 10 is relatively low, resulting in poor flame retardancy of the board, only V-1 level. Compared with Example 1, the amount of phosphorus-containing flame retardant used in Comparative Example 11 is higher, resulting in a decrease in Tg of the board and a deterioration in T288 heat resistance.
[0122] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the halogen-free flame retardant resin composition, the prepreg containing the same, the metal foil-clad laminate and the printed circuit board of the present invention, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the scope of protection and disclosure of the present invention.
Claims
1. A halogen-free flame retardant resin composition, characterized in that: The halogen-free flame retardant resin composition comprises the following components in parts by weight: Epoxy resin A: 100 parts by weight; Low dielectric curing agent B: 10-75 parts by weight; Benzoxazine prepolymer C: 5-40 parts by weight; Side chain epoxy modified silicone oil D: 0.001-5 parts by weight; Phosphorus-containing flame retardant E: 20-50 parts by weight.
2. The halogen-free flame retardant resin composition according to claim 1, characterized in that: The epoxy resin is selected from any one of a trifunctional epoxy resin or a tetrafunctional epoxy resin or a combination of at least two thereof; Preferably, the epoxy resin is selected from any one or a combination of at least two of dicyclopentadiene epoxy resin, dimethylphenol novolac epoxy resin, tetramethyl biphenyl epoxy resin, biphenyl epoxy resin, novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, epoxy resin containing C1-C6 alkyl, MDI modified epoxy resin, epoxy resin containing naphthalene ring or epoxidized polybutadiene.
3. The halogen-free flame retardant resin composition according to claim 1 or 2, characterized in that: The low dielectric curing agent includes anhydride curing agent and / or active ester curing agent; Preferably, the anhydride curing agent is selected from any one of the following B11 or B12 or a combination of at least two: Wherein, n:x=1:1 to 8:1; Preferably, the content of the anhydride curing agent in the low dielectric curing agent is 1-50 parts by weight.
4. The halogen-free flame retardant resin composition according to any one of claims 1 to 3, characterized in that: The active ester curing agent is selected from any one or a combination of at least two of the active esters having the following B21 or B22 structures: In B21, X is phenyl or naphthyl, j is 0 or 1, k is 0 or 1, and n represents a repeating unit of 0.25 to 1.25; In B21, m, n, and q are independently integers of 1 to 6, X is phenyl or naphthyl, and Y is the following group: Where K is 0 or 1.
5. The halogen-free flame retardant resin composition according to any one of claims 1 to 4, characterized in that: The benzoxazine prepolymer C is a benzoxazine oligomer containing phenolic hydroxyl groups generated by the self-polymerization reaction of benzoxazine monomers, or a prepolymer formed by further copolymerization of benzoxazine oligomers and epoxy resins; Preferably, the number average molecular weight Mn of the benzoxazine prepolymer is 500-1000; Preferably, the GT of the benzoxazine prepolymer is 50-300s.
6. The halogen-free flame retardant resin composition according to any one of claims 1 to 5, characterized in that: The side chain epoxy modified silicone oil D has the following structure: Wherein, m and n are each an integer greater than 1; R1 is independently selected from the functional groups of the following structures: R2 is a C1-C5 alkyl group, or a C1-C5 alkyl structure containing an ether bond, or a C1-C5 aryl alkyl structure containing a phenyl group; Preferably, the epoxy equivalent of the side chain epoxy-modified silicone oil D is ≤4000 g / mol.
7. The halogen-free flame retardant resin composition according to any one of claims 1 to 6, characterized in that: The phosphorus-containing flame retardant is selected from inorganic phosphorus-containing flame retardants and / or organic phosphorus-containing flame retardants; Preferably, the inorganic phosphorus flame retardant is selected from any one or a combination of at least two of red phosphorus, ammonium phosphate, phosphoric acid amide, phosphoric acid or phosphine oxide; Preferably, the ammonium phosphate includes any one of monoammonium phosphate, diammonium phosphate or triammonium phosphate, or a combination of at least two thereof; Preferably, the organic phosphorus flame retardant is selected from any one or a combination of at least two of aromatic phosphates, monosubstituted phosphonic acid diesters, disubstituted phosphinates, metal salts of disubstituted phosphinic acids, cyclic organic phosphorus compounds, or phosphorus-containing phenolic resins; preferably any one or a combination of at least two of aromatic phosphates, metal salts of disubstituted phosphinic acids, or phosphorus-containing phenolic resins, and more preferably phosphorus-containing phenolic resins; Preferably, the halogen-free flame retardant resin composition further comprises a filler F; Preferably, the filler is selected from any one or a combination of at least two of aluminum hydroxide, silicon dioxide, talc, boehmite, zeolite, wollastonite, magnesium oxide, calcium silicate, calcium carbonate, clay or mica; Preferably, the median particle size of the filler is D50 = 1.8-3.2 μm, and the maximum particle size is D100 = 5.0-15.0 μm; Preferably, the physical form of the filler is flake, rod, sphere, hollow sphere, granule, fiber or plate; Preferably, relative to 100 parts by weight of epoxy resin A, the content of filler in the halogen-free flame retardant resin composition is 40-400 parts by weight; Preferably, the halogen-free flame retardant resin composition further comprises a curing accelerator G; Preferably, the curing accelerator is selected from any one of imidazole accelerators, pyridine curing agents, Lewis acid curing agents, amine curing agents, phenolic curing agents, cyanate compounds or active ester compounds, or a combination of at least two thereof.
8. A prepreg, characterized in that: The prepreg comprises the halogen-free flame retardant resin composition according to any one of claims 1 to 7.
9. A metal foil-clad laminate, characterized in that: The metal foil-clad laminate comprises at least one prepreg as claimed in claim 8 and a metal foil coated on one side or both sides of the stacked prepreg.
10. A printed circuit board, characterized in that: The printed circuit board includes at least one of the prepreg according to claim 8 or the metal foil clad laminate according to claim 9.
Citation Information
Patent Citations
Low dielectric resin composition, copper foil and preparation method and application thereof
CN114702785A
Halogen-free flame-retardant resin composition, prepreg, laminated board and printed circuit board
CN115819929A
Resin glue solution, prepreg, metal foil-coated laminated board and printed circuit board
CN116376230A
Resin composition, prepreg, and printed wiring board therewith
JP2004182851A
Resin compositions and products thereof
TWI742692B